Establishment and Application of Peristaltic Human Gut-Vessel Microsystem for Studying Host–Microbial Interaction - Jing, Bolin; Wang, Zhuo A.; Zhang, Chen; Deng, Quanfeng; Wei, Jinhua; Luo, Yong; Zhang, Xiuli; Li, Jianjun; Du, Yuguang (Frontiers in Bioengineering and Biotechnology, 2020)
Intestinal floras influence a lot of biological functions of the organism. Although animal model are strong tools for researches on the relationship between host and microbe, a physiologically relevant in vitro human gut model was still required. Here, a novel human gut-vessel microfluidic system was established to study the host–microbial interaction. Peristaltic motion of the cells on the chip was driven by a pneumatic pump. When intestinal epithelial cells (Caco2) were co-cultured with vascular endothelial cells (HUVECs) on the peristaltic microfluidic chip, Caco2 showed normal barrier and absorption functions after 5 days cultivation, which generally took 21 days in static Transwell models. Intestinal microvilli and glycocalyx layer were seen after 4 days cultivation, and Lactobacillus casei was successfully co-cultured for a week in the intestinal cavity. A model for intestinal damage and inflammatory responses caused by E. coli was set up on this chip, which were successfully suppressed by Lactobacillus casei or antibiotic. In summary, this human gut-vessel microfluidic system showed a good potential for investigating the host–microbial interaction and the effect and mechanism of microbiome on intestinal diseases in vitro.